Petrarch and Boccaccio : the Unity of Knowledge in the Pre-modern World - Candido, Igor (Mimesis ;, 2018)
The early modern and modern cultural world in the West would be unthinkable without Petrarch and Boccaccio. Despite this fact, there is still no scholarly contribution entirely devoted to analysing their intellectual revolution. Internationally renowned scholars are invited to discuss and rethink the historical, intellectual, and literary roles of Petrarch and Boccaccio between the great model of Dante's encyclopedia and the ideas of a double or multifaceted culture in the era of Italian Renaissance Humanism. In his lyrical poems and Latin treatises, Petrarch created a cultural pattern that was both Christian and Classical, exercising immense influence on the Western World in the centuries to come. Boccaccio translated this pattern into his own vernacular narratives and erudite works, ultimately claiming as his own achievement the reconstructed unity of the Ancient Greek and Latin world in his contemporary age. The volume reconsiders Petrarch's and Boccaccio's heritages from different perspectives (philosophy, theology, history, philology, paleography, literature, theory), and investigates how these heritages shaped the cultural transition between the end of the Middle Ages and the early modern era, as well as European identity.